2001
DOI: 10.1021/ie010195z
|View full text |Cite
|
Sign up to set email alerts
|

Surface Diffusion of Adsorbed Molecules in Porous Media:  Monolayer, Multilayer, and Capillary Condensation Regimes

Abstract: This review provides an overview of surface diffusion and capillary condensate flow in porous media. Emphasis has been placed on the distinction between purely surface diffusion, multilayer surface diffusion, and capillary condensate flow.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
182
1
1

Year Published

2003
2003
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 245 publications
(190 citation statements)
references
References 135 publications
(314 reference statements)
5
182
1
1
Order By: Relevance
“…Diffusion of OCS in the adsorbed phase can theoretically occur and can be described in a similar fashion to other trace gases (e.g. see Choi et al (2001) for ozone). However we will neglect such a diffusion flux in the adsorbed phase because it is expected to be orders of magnitude smaller than in the two other phases.…”
Section: Diffusive Fluxesmentioning
confidence: 99%
“…Diffusion of OCS in the adsorbed phase can theoretically occur and can be described in a similar fashion to other trace gases (e.g. see Choi et al (2001) for ozone). However we will neglect such a diffusion flux in the adsorbed phase because it is expected to be orders of magnitude smaller than in the two other phases.…”
Section: Diffusive Fluxesmentioning
confidence: 99%
“…It has been reported that surface diffusion of most organic fluids in typical porous materials is reduced by roughly an order of magnitude from that of the pure liquid. 19,20 Since the diffusion of pure methanol 21 is 1.6 × 10 −9 m 2 /s, this is expected to be on the order of 10 −10 m 2 /s . This reduction can be largely attributed to the geometrical form factor often represented by the phenomenological relation known as Archie's Law.…”
Section: Theorymentioning
confidence: 99%
“…Experimental studies have shown that surface diffusion contributes significantly to the total diffusive flux in both mesoporous and microporous systems [2,3]. There are examples where the surface diffusion accounts for more than 50% of the total mass flow rate [4,5].…”
Section: Introductionmentioning
confidence: 99%
“…Today, there are basically three different approaches in modeling surface diffusion; mechanistic (hopping) model, random walk (Fick's law) model and hydrodynamic (slip) model [4,6]. Fick's law approach is the most widespread in use [4,6] and assumes that the gaseous and the surface fluxes are independent of each other [6].…”
Section: Introductionmentioning
confidence: 99%